Detection of Macrobenthos Species With Metabarcoding Is Consistent in Bulk DNA but Dependent on Body Size and Sclerotization in eDNA From the Ethanol Preservative - Derycke, Sofie; Maes, Sara; Van den Bulcke, Laure; Vanhollebeke, Joran; Wittoeck, Jan; Hillewaert, Hans; Ampe, Bart; Haegeman, Annelies; Hostens, Kris; De Backer, Annelies (Frontiers in Marine Science, 2021)
DNA metabarcoding is a promising method to increase cost and time efficiency of marine monitoring. While substantial evidence exists that bulk DNA samples adequately reflect diversity patterns of marine macrobenthos, the potential of eDNA in the ethanol preservative of benthic samples for biodiversity monitoring remains largely unexplored. We investigated species detection in bulk DNA and eDNA from the ethanol preservative in samples from four distinct macrobenthic communities in the North Sea. Bulk DNA and eDNA were extracted with different extraction kits and five COI primer sets were tested. Despite the availability of a nearly complete reference database, at most 22% of the amplicon sequence variants (ASVs) were assigned taxonomy at the phylum level. However, the unassigned ASVs represented only a small fraction of the total reads (13%). The Leray primer set outperformed the four other primer sets in the number of non-chimeric reads and species detected, and in the recovery of beta diversity patterns. Community composition differed significantly between bulk DNA and eDNA samples, but both sample types were able to differentiate the four communities. The probability of detecting a species in the eDNA from the ethanol preservative was significantly lower than for bulk DNA for macrobenthos species having small to medium body size and for species having chitine or CaCO3 in their cuticula. Detection in the bulk DNA samples was not affected by the investigated morphological traits, indicating that monitoring of macrobenthos species will be most robust when using bulk DNA as template for metabarcoding.